MANAGERIAL CULTURE – “MENTAL EQUIPMENT” AT THE EMPLOYEES DISPOSAL IN THE TOURISM UNITS - Constanţa ENEA (Management & Marketing, 2009)
Environmental adaptation and behavioral integration are two major problemsthe organization of this beginning of century is confronting with.Organizational culture is one of the solutions to solving these problems. Thispaper presents the characteristics of organizational culture and the degree ofinfluence on it by the different levels of managers. The most important part ofthe paper presents how managers can change the culture of organizationsthrough influencing the cultural web of it.